Analisis Kualitas Layanan dan Kepuasan Konsumen Pengguna Jasa Rumah Sakit Islam Nashrul Ummah - Ulum, Miftachul; Mun'im, Abdul; Maghfuri, Rahmah Salsabila Al (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
This research wants to describe the influence of service quality and service user satisfaction at the Nashrul Ummah Islamic Hospital. The analytical method used is multiple regression analysis. Service quality variables include Reliability (X1), Responsiveness (X2), Confidence (X3), Empathy (X4) and Satisfaction variables (Y). Data collection was done by distributing numbers to 50 respondents as service users. The research results show that service quality consisting of Reliability (X1), Responsiveness (X2), Confidence (X3), Empathy (X4) has significant variables on Satisfaction (Y). This research also shows that the responsiveness variable is very dominant in its influence on satisfaction